Computer vision versus wearables assessment of the up-on-the-toes 30-second test - R. Jaber; S.A. Zahid; A.L.F Rodacki; R. Qahwaji; J.G. Buckley (Computer Methods in Biomechanics and Biomedical Engineering: Imaging & Visualization)
The rising up-on-the-toes (UTT) 30-second test is used clinically to assess ankle muscle strength and endurance. Typically, the test is subjectively evaluated by counting how many UTT movements are completed. We have recently shown that the UTT test can be objectively assessed using signals from small inertial measurement units (IMUs). The current study investigates whether computer vision (CV) analysis of the UTT test gives comparable outcomes to IMU analysis. A CV-based system was applied to video recordings of 29 older adult participants (76.0 ± 4.3 years) performing the UTT test with IMUs attached to their feet. Angular velocity time series signals were generated using both IMU and video object detection of the right foot landmarks, enabling peak plantarflexion velocities during the ascent and descent phases to be extracted. Findings demonstrate that the CV-based approach produces closely aligned output metrics with IMU data, with coefficient of determination (R2) values of ≥0.91.